2019
DOI: 10.1155/2019/3414678
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Schwannoma: A Clinicopathological, Immunohistochemical, and Prognostic Study of 9 Cases

Abstract: Background. Intestinal schwannoma is a type of intestinal interstitial tumor with a very low incidence. At present, there are few studies on intestinal schwannoma. Methods. From January 2010 to January 2018, the patients diagnosed with intestinal schwannoma at the China-Japan Union Hospital of Jilin University were retrospectively reviewed. The patients’ clinicopathological features and prognosis were analyzed. Results. This study enrolled 9 patients with intestinal schwannoma, including 3 males and 6 females.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 36 publications
2
34
1
2
Order By: Relevance
“…Schwannomas are tumors arising from Schwan cells of the neural sheath [1]. They are most commonly found in the central nervous system, spinal cord, and peripheral nerves in the extremities [2]. Gastrointestinal schwannomas (GS), which originate from Auerbach's nerve plexus in the muscularis propria, are extremely rare [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schwannomas are tumors arising from Schwan cells of the neural sheath [1]. They are most commonly found in the central nervous system, spinal cord, and peripheral nerves in the extremities [2]. Gastrointestinal schwannomas (GS), which originate from Auerbach's nerve plexus in the muscularis propria, are extremely rare [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Because GS are rare and easily confused with a heterogeneous group of neuroectodermal or mesenchymal neoplasms such as gastrointestinal stromal tumors (GISTs), leiomyomas, neurofibromas, and glomus tumors, the preoperative diagnostic accuracy is quite low. Accurate diagnosis is established by postoperative pathology and immunohistochemistry [2,6,9].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that common serum tumor markers, such as fetoprotein, CEA and carcinoembryonic antigen, were within the normal range (42,43), but occasionally increased CA19-9 was observed (44). Notably, Shu et al (45) pointed out that one patient had elevated serum neuron-specific enolase (NSE) levels. NSE is an acid protease that is specific to neurons and neuroendocrine cells, and is highly concentrated in nerve cells, neuroendocrine cells and tumor cells (45).…”
Section: Common Auxiliary Examinations and Characteristicsmentioning
confidence: 99%
“…Nuclear palisading and well‐formed Verocay bodies are only occasionally seen . The presence of a peripheral cuff of lymphoid aggregates helps to distinguish from GIST . Myxoid stroma may be a helpful diagnostic clue.…”
Section: Schwannomamentioning
confidence: 99%
“…Both soft tissue and colorectal schwannomas are diffusely positive for S100, but in contrast to their soft tissue counterpart, glial fibrillary acidic protein (GFAP) is positive in only a small proportion (5%) of colorectal schwannomas . Tumour cells are negative for muscle markers and CD117 . A positive cytokeratin stain should alert the pathologist to the possibility of an alternative diagnosis (e.g.…”
Section: Schwannomamentioning
confidence: 99%